Tracing the Roots of Corruption Problems in Village Governance - Syofian (International Conference On Law And Social Sciences, 2024)
Corruption remains a persistent challenge in government structures rural villages, undermining development efforts and eroding trust public against local authorities. This article aims to dive into networking Complicating factors that cause corruption in the village government system. By examining socio-economic dynamics, cultural influences, weaknesses institutional, and political pressures at play, this study seeks to trace root causes of corruption at the grassroots level. Through comprehensive analysis of case studies and empirical evidence, this article reveals the nature of the various dimensions corruption in village administration. Additionally, this article proposes strategies and interventions to address these underlying issues effectively, foster transparency, accountability and integrity in rural government practices. This research emphasizes the importance of understanding and confronting the causes main corruption to build a strong and ethical village government system.